2014
DOI: 10.1002/asia.201403165
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Nitronyl Nitroxide‐Based 3d–4f Clusters: Structure and Magnetism

Abstract: Three unprecedented nitronyl nitroxide radical-bridged 3d-4f clusters, [Ln2 Cu2 (hfac)10 (NIT-3py)2 (H2 O)2 ](Ln(III) =Y, Gd, Dy), have been obtained from the self-assembly of Ln(hfac)3 , Cu(hfac)2 , and the radical ligand. The Dy complex shows a slow relaxation of magnetization, representing the first nitronyl nitroxide radical-based 3d-4f cluster with single-molecule magnet behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The metal-radical heterospin strategy, in which metal ions link with stable organic radicals, is extremely fascinating for designing molecular magnetic materials [1][2][3][4][5][6]. Based on this kind of heterospin approach, 3d [7][8][9], 4f [10][11][12][13][14][15][16][17], and 3d-4f [18][19][20][21][22][23] compounds have been obtained so far by employing various organic radicals, such as N 2 3− [15,16], HAN 3− [24], TTF + [25], thiadiazoyl [14], and nitronyl nitroxide radical ligands [6,7,10,13,19,23,[26][27][28][29][30][31][32]. In particular, nitronyl nitroxide radicals are often used as building blocks to construct metal compounds with various topology structures due to the substituent groups of nitronyl nitroxides being able to effectively regulate the spatial arrangement of magnetic building blocks [33].…”
Section: Introductionmentioning
confidence: 99%
“…The metal-radical heterospin strategy, in which metal ions link with stable organic radicals, is extremely fascinating for designing molecular magnetic materials [1][2][3][4][5][6]. Based on this kind of heterospin approach, 3d [7][8][9], 4f [10][11][12][13][14][15][16][17], and 3d-4f [18][19][20][21][22][23] compounds have been obtained so far by employing various organic radicals, such as N 2 3− [15,16], HAN 3− [24], TTF + [25], thiadiazoyl [14], and nitronyl nitroxide radical ligands [6,7,10,13,19,23,[26][27][28][29][30][31][32]. In particular, nitronyl nitroxide radicals are often used as building blocks to construct metal compounds with various topology structures due to the substituent groups of nitronyl nitroxides being able to effectively regulate the spatial arrangement of magnetic building blocks [33].…”
Section: Introductionmentioning
confidence: 99%
“…10 right). 37 The central core resulted from the coordination of the radical units to two Cu centers by the pyridine fragment and by one of its two NO units respectively; two The assemblage of 3-pyridine substituted nitronyl nitroxide with Ln(hfac) 3 and Cu(hfac) 2 yielded the discrete complexes [Ln 2 Cu 2 (hfac) 10 (Nit-3py) 2 (H 2 O) 2 ] (13, Ln = Y, Gd, Dy) characterized by a cyclic [Cu 2 Nit-3py 2 ] (Nit-3py = 2-(3-pyridyl)-4,4,5,5tetramethylimidazoline-1-oxyl-3-oxide) coordinating to two Ln(hfac) 3 units (Fig.…”
Section: Zero-dimensional Compoundsmentioning
confidence: 99%
“…In these architectures, significant magnetic coupling can be observed that induces 0-, 1-, 2-or 3-dimensional overall magnetic behaviors. [25][26][27][28][29][30][31][32][33] Such materials can also give rise to unique magnetic behavior such as next-nearest neighbor interactions, 34 one-dimensional helimagnetism [35][36][37] or Single…”
Section: Introductionmentioning
confidence: 99%